ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN PERTAMBANGAN DI INDONESIA - Cahyo Kurniawan; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2015)
This research aims to analyze the effect of the variables in predicting the company's capital structure. The variables in this research consist of free cash flow (FCF), tangible assets (TAN), firm size (SIZ), and profitability (PRO). The population of this study was all  mining company listed in Indonesia Stock Exchange (ISX) in 2009-2013. Sampling was done by using purposive sampling method and obtain 23 companies with a total of 115 data in this research period. This research used multiple linear regression analysis for testing the influence of independent variables on dependent variable.Results from this research showed that free cash flow significantly and have an influence on the increase or decrease the company's capital structure. Tangible assets and profitability negative significantly influence to the mining company's capital structure. Firm size did not significantly influence to the mining company's capital structure.